Sinterização de nanopartículas de NiAl2O4 por gelatina comestível - Nogueira, Núbia Alves de Souza (2005)
In this work, the gelatin was used as organic precursor in order to produce nanoparticle of nickel aluminate (NiAl2O4). Six sets of solution were prepared with gelatin, water and salts of Ni (NiCl2.6H2O) and Al (AlCl36H2O) or (Al (NO3) 39H2O) at Ni: Al = 1:4 ratio, which five one were submitted to drying process first and afterward synthesizing at 500, 600, 700, 800, 900 and 1000oC with the temperature rating of 10o C/min. iThe last sets were prepared following the same procedure but however the temperature was kept at 800oC and the sintering time was varied (12, 9, 6 and 3 hours). For the temperatures above 700oC, the particle size of NiAl2O4 was uniform and for 800oC was obtained the smallest particle size (5nm). X-ray powder diffraction pattern were obtained for all samples and the Rietveld Method was applied in order to get the particle size, by means of Scherrer's equation, lattice parameter, nanoparticle morphology and phase concentration. The particle size was compared with particle size obtained by Williamson-Hall´s plot and the microstrain as well. After drying process, some samples were submitted to thermogravimetric analysis (TGA) DSC and B.E.T., to determine the loss weight, the energy involved during the heating and the surface area, respectively.